PENGARUH KOMPENSASI, DAN WORKLIFE BALANCE TERHADAP KINERJA DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERASI PADA PEGAWAI DINAS KESEHATAN PROVINSI JAWA TENGAH - Rijanti, Tristiana; Santoso, Agus Budi; Indriyaningrum, Kis; Kurnia, Dyna (Proceeding SENDI_U, 2021)
This study aims to analyze the influence of compensation and worklife balance on employee performance with organizational culture as moderating variable at the Central Java Provincial Health Office. The population in this study were all employees of the Central Java Provincial Health Office with 200 respondents. The sample technique used is purposive sampling with 90 respondents.The test in this study consisted of test instruments, namely validity and reliability tests and hypothesis testing with multiple linear regression. The results of the analysis show that: Compensation has a positive and significant effect on performance, worklife balances has a positive and significant effect on performance, and organizational culture is proven to be a moderating variable that strengthens the influence of both compensation on performance and worklife balance on performance.